Secularisation and intimate relationships in a Catholic community: Is Malta a resistant niche? - Deguara, Angele (Social compass, 2020)
This study explores secularisation in a traditionally Catholic community through the analysis of intimate relationships which fall outside Catholic morality. It gives an indication of how individuals in contemporary society perceive Church teachings on sexuality in terms of the relationship choices they make. The research draws upon 2 years of fieldwork carried out with Drachma LGBTI, a space where lesbian, gay, bisexual, trans, and intersex (LGBTI) people of faith may explore and deepen their spirituality. I also conducted 35 in-depth interviews with LGBT and non-LGBT individuals whose lifestyle runs counter to official Church teachings on sexuality, despite their Catholic faith that is, who are in a same-sex relationship or else divorced, cohabiting or in a civil marriage. The study revealed that while informants may disregard Church teachings on matters of sexuality, their reconstructed sexual morality is still embedded within a Catholic framework.